The Necessity of a Jewish Systematic Theology - Alana M. Vincent (Svensk Teologisk Kvartalskrift, 2017)
Taking into account current disputes about the nature of theology and religious studies, both inside and outside of the academy, this article argues that the academic discipline of theology would benefit greatly by expanding its religious remit beyond the traditional field of Christian systematic theology to include constructive-critical insider engagement with the texts of other traditions – e.g., Jewish and Islamic theology.